Embracing God as Father : Christian identity in the family of God - Bush, Daniel; Due, Noel (Lexham Press, 2015)
The image of the Prodigal Father is striking--God searches for the lost and weary to save them. Once saved, we are adopted into his family, through Christ, to become sons and daughters of the one and only Father. In this theologically rich and deeply personal book, Daniel Bush and Noel Due show us the loving heart of the Father toward his children. Jesus said, "Whoever has seen me has seen the Father" (John 14:9)--he and the Father are one in their love, joy, and desire to bless. Embracing God as Father helps us see God as he truly is and see who we are as his sons and daughters.--Publisher description.